Pengaruh Work Life Balance dan Pemberdayaan Terhadap Produktivitas Tenaga Medis Generasi Milenial - Sari, Ajeng Kartika; Nurhidayah, Nurhidayah; Basalamah, Muhammad Ridwan; Pramudito, Ekvan Danang Setya (Jurnal Ilmiah Global Education, 2025)
This study aims to examine the influence of work-life balance and empowerment on the productivity of millennial doctors in Indonesia, given that this group dominates the medical workforce and faces increasing systemic challenges. The research method used is an explanatory quantitative approach with data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 3.0 software. The research sample consisted of 100 millennial doctors in Indonesia, who were selected using purposive sampling. The results showed that work-life balance does not have a significant direct influence on the productivity of millennial medical personnel (p-value = 0.276), but has a positive influence on empowerment (p-value = 0.000). In addition, empowerment is shown to have a significant positive influence on productivity (p-value = 0.000), and empowerment also acts as a mediator that strengthens the relationship between work-life balance and millennial medical personnel productivity, empowerment also acts as a catalytic mechanism that transforms work-life balance experiences into improved professional performance. This dimension is in line with previous research. These findings highlight the importance of empowerment in creating a work ecosystem that supports work-life balance and improves productivity. Policies that integrate empowerment with work-life balance can create a conducive work environment for millennial doctors, which not only improves their well-being but also enables them to achieve optimal performance. Therefore, the development of policies that support these two factors will contribute to the quality of medical services in Indonesia.